Distributed cognition and the will : individual volition and social context - Ross, Don (A Bradford Book, 2007)
Philosophers and behavioral scientists discuss what, if anything, of the traditional concept of individual conscious will can survive recent scientific discoveries that human decision-making is distributed across different brain processes and through the social environment.